Renal Cell Carcinoma With TFEB Translocation Versus Unclassified Renal Cell Carcinoma With TFEB Amplification. Issue 6 (November 2017) - Martin, Elizabeth E.; Mehra, Rohit; Jackson-Cook, Colleen; Smith, Steven Christopher
Abstract : Abstract: Microphthalmia transcription factor (MiT)–family translocation renal cell carcinomas (RCCs) are an unusual but increasingly recognized group of RCC defined by recurrent gene rearrangements involving the TFE3 or TFEB loci. These genes belong to the MiT family, imparting a unique expression of melanocytic markers seen in these tumors. The Xp11 translocation RCCs are more common and better studied than their t(6;11) translocation RCC counterpart, and the newly emerging entity of TFEB -amplified RCC (technically falling under the unclassified category of RCC) has emerged only as a few case reports and small series. Herein, we present 2 cases with careful workup, followed by a discussion of MiT family translocation RCC, particularly t(6;11) translocation RCC and TFEB -amplified RCC. We will emphasize the clinical and epidemiological features, including emerging potential prognostic differences, the gross and microscopic findings for the tumors, and the immunohistochemical and molecular findings to date, including changes at the TFEB locus. We also discuss the differential diagnosis of these tumors with recommendations for prospective practice.